2017
DOI: 10.1055/s-0037-1605561
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Sagittal and Axial Alignments of Patella after Open- and Closed-Wedge High-Tibial Osteotomy: A Systematic Review and Meta-Analysis

Abstract: The present systematic review and meta-analysis were aimed to verify the effect of open-wedge (OW) and closed-wedge (CW) high-tibial osteotomy (HTO) on sagittal and axial alignments of the patella. A vigorous search was performed for studies that compared the changes of sagittal and axial alignments of patella after OW and CW HTO. After evaluating publication bias and heterogeneity, we aggregated variables by using the random-effects model. The weighted mean differences in sagittal and axial alignment of patel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…The change in patellar height after HTO could be the result of various factors, such as patellar ligament scarring due to immobilization, change in sagittal tibial slope, as well as elevation or depression of the tibial plateau. In the metaanalysis by Lee et al [17], the reduction in patellar height after open-wedge HTO according to the Blackburne-Peel (mean, -0.10) and Caton-Deschamps (mean: -0.08) indices were identical to those measured in the present study (-0.10 and -0.08, respectively). A decrease in patellar height could result in patella baja, which can compromise patellofemoral biomechanics, and could require subsequent total knee arthroplasty (TKA) [17].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The change in patellar height after HTO could be the result of various factors, such as patellar ligament scarring due to immobilization, change in sagittal tibial slope, as well as elevation or depression of the tibial plateau. In the metaanalysis by Lee et al [17], the reduction in patellar height after open-wedge HTO according to the Blackburne-Peel (mean, -0.10) and Caton-Deschamps (mean: -0.08) indices were identical to those measured in the present study (-0.10 and -0.08, respectively). A decrease in patellar height could result in patella baja, which can compromise patellofemoral biomechanics, and could require subsequent total knee arthroplasty (TKA) [17].…”
Section: Discussionsupporting
confidence: 82%
“…In the metaanalysis by Lee et al [17], the reduction in patellar height after open-wedge HTO according to the Blackburne-Peel (mean, -0.10) and Caton-Deschamps (mean: -0.08) indices were identical to those measured in the present study (-0.10 and -0.08, respectively). A decrease in patellar height could result in patella baja, which can compromise patellofemoral biomechanics, and could require subsequent total knee arthroplasty (TKA) [17]. Furthermore, revision to TKA can be challenging in knees with patella baja, though patellar eversion or patellar tendon avulsion remains straightforward if reductions in patellar height are small [3].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Some studies addressed that OWHTO results in a decrease in the patellar height which may lead to patella baja. [12][13][14][15][16][17][18] Some studies highlighted that the change in patellar height also affects patellar tracking, which also results in alterations in patellofemoral congruency, and contact stress would thus increase cartilage pressure and lead to patellofemoral degeneration or patellofemoral OA. 17,[19][20][21] In contrast, some studies reported that the changes in patellofemoral alignment do not have a clinical impact after OWHTO.…”
mentioning
confidence: 99%
“…In addition, the patellofemoral joint on the sagittal plane is also influenced by the operation [2]. Several studies have shown that OWHTO causes patellar infera, increases patellofemoral joint pressure pain, increases the risk of patellofemoral OA progression, and makes it more difficult for total knee arthroplasty to be performed in the future [3][4][5][6][7][8]. Kim et al [8] reported the prevalence of the progression of patellofemoral OA to be 41.2% in the femoral trochlea and 21.9% in the patella articular surface after more than 2 years in 114 patients who underwent OWHTO.…”
Section: Introductionmentioning
confidence: 99%